Characterization of a Bacterium Isolated from Hydrolyzed Instant Sea Cucumber Apostichopus japonicus Using Whole-Genome Sequencing and Metabolomics - Xin Luo; Zhixuan Zhang; Zhangyi Zheng; Wenwen Zhang; Tinghong Ming; Lefei Jiao; Xiurong Su; Jiajie Xu; Fei Kong (Foods)
Autolysis in the sea cucumber Apostichopus japonicus is typically triggered by degradation caused by microorganisms within their bodies. However, information on this topic remains limited. Recently, we isolated and purified a bacterial strain from hydrolyzed instant sea cucumber samples. To investigate its potential role in the autolysis process, this study employed whole-genome sequencing and metabolomics to explore its genetic and metabolic characteristics. The identified strain was classified as Lysinibacillus xylanilyticus and designated with the number XL-2024. Its genome size is 5,075,210 bp with a GC content of 37.33%, encoding 5275 genes. Functional database comparisons revealed that the protein-coding genes were distributed among glucose metabolism hydrolase, metal hydrolase, lysozyme, cell wall hydrolase, and CAZymes. Compared to 20 closely related strains, L. xylanilyticus XL-2024 shared 1502 core homologous genes and had 707 specific genes. These specific genes were mainly involved in the carbohydrate metabolism pathway and exhibited glycosyl bond hydrolase activity. Metabolomic analysis showed that L. xlanilyticus XL-2024 produced several metabolites related to polysaccharide degradation, including peptidase, glucanase, and pectinase. Additionally, the presence of antibacterial metabolites such as propionic acid and ginkgo acid among its metabolites may enhance the stability of the sea cucumber hydrolysate. In summary, L. xylanilyticus XL-2024 may play a pivotal role in the autolysis of A. japonicus. The results of this study provide a strong foundation for understanding how to prevent autolysis in A. japonicus and for better utilizing L. xylanilyticus XL-2024.